A cross-cultural comparison of sleep patterns between typically developing children and children with ASD living in Saudi Arabia and the United Kingdom. (September 2022) - Bin Eid, W.; Lim, M.; Halstead, E.; Esposito, G.; Dimitriou, D.
Abstract: Background: Sleep is crucial for child development, especially for children with ASD. While it is known that children with ASD experience more severe sleep problems and that these problems tend to persist compared to their typically developing counterparts, these findings tend to come from only Western countries. A cross-cultural study is important to understand if the prevailing understanding of sleep in children with ASD can be extended to different cultural backgrounds. Aim: A cross-cultural study is conducted, involving typically developing children and children with ASD aged 5–12 across two countries: Saudi Arabia and the United Kingdom. Methods and procedures: Using a combination of questionnaires measuring ASD severity (CARS-2), sleep quality (CSHQ), sociodemographic and lifestyle variables and sleep diaries, 244 children were sampled using a mixture of snowball and convenience sampling methods. Outcomes and results: Children with ASD experience more sleep problems compared to typically developing children in Saudi Arabia, and these problems similarly persist across time. Specifically, it was found that children with ASD in Saudi Arabia experience greater sleep onset latency and a greater number of night awakenings. Additionally, across the ASD groups, it was found that children from Saudi Arabia generally experienced poorer sleep than children in the United Kingdom in terms of shorter sleep duration, although children in the United Kingdom tended to report more instances of sleep anxiety and parasomnias. Conclusions and implications: Several reasons such as parental education about sleep hygiene, cultural influences and social hours were put forward as potential explanations for cross-cultural differences. Findings served to emphasise the importance of culturally-appropriate interventions and public education regarding child sleep. Highlights: Children in Saudi Arabia have short sleep duration averaging 6 h. Sleep hygiene is not commonly practised in Saudi Arabia. Parental awareness about sleep in Saudi Arabia is not evident.